anonymous
  • anonymous
For a geometric sequence, a1 = -2 r=2 and an= -64. Find n and Sn The n's are subscript, but I don't know how to type them like that on here.
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
A geometric sequence is much like a geometric series in that the formula is as follows: \[a_{n}=ar^{n}\] when n starts at 0 or\[a_{n}=ar^{n-1}\] when n starts at 1. Since you are given \[a_{1} = -2\] Then we will use the \[a_{n}=ar^{n-1}\]formula because that starts at n=1, so n can be deduced by plugging the values given in the formula, i.e.\[a_{1}=-2=ar^{1-1}=ar^{0}=a\]\[a_{n}=-64=-2*r^{n-1}\]\[-64/-2=2^{n-1}=2^{n}2^{-1}\]\[64/2=2^{n}/2\]\[64=2^{n}\]\[\log_{2}(64)=n=6\]So this saya that the last value in the sequence is -64 and that term is n=6. Sn is in the next post
anonymous
  • anonymous
From above, \[s_{n}=ar^{1-1}+ar^{2-1}+ar^{3-1}+...+ar^{n-1}\] \[s_{n}=a+ar+ar^{2}+...+ar^{n-1}\] Now if we multiply r on both sides of this equation, we get \[rs_{n}=ar+ar^{2}+ar^{3}+...+ar^{n-1}r\] The last term is \[ar^{n-1}r=ar^{n-1+1}=ar^{n}\] Subtract rSn from Sn \[s_{n}-rs_{n}=a+ar+ar^{2}+...+ar^{n-1} -\] \[ (ar+ar^{2}+ar^{3}+...+ar^{n})\] Notice that all the terms cancel each other except the first and the last. \[s_{n}-rs_{n}=a-ar^{n}\]\[s_{n}(1-r)=a(1-r^{n})\]\[s_{n}=a(1-r^{n})/(1-r)=-2(1-2^{n})/(-1)=2(1-2^{n})\]Knowing that a1=a

Looking for something else?

Not the answer you are looking for? Search for more explanations.